Prognostic Signature of Hepatocellular Carcinoma and Analysis of Immune Infiltration Based on m6A-Related lncRNAs - Guo, Ting; He, Kun; Wang, Yifei; Sun, Jingjing; Chen, Yong; Yang, Zelong (Frontiers in Oncology, 2021)
The relationship between m6A-related lncRNAs and prognosis in hepatocellular carcinoma (HCC) is not yet clear. We used Lasso regression to establish a prognostic signature based on m6A-related lncRNAs using a training set from TCGA, and then verified the signature efficacy in a test set. Fluorescence quantitive real-time PCR (qPCR), Survival analysis, clinical risk difference analysis, immune-related analysis, and drug-sensitivity analysis were conducted. The results revealed that 1651 lncRNAs were differentially expressed in HCC tissues, among which 163 were m6A-related. Univariate analysis showed that 87 lncRNAs were associated with overall survival. Six differential m6A-related lncRNAs were validated and selected via Lasso regression to construct a prognostic signature which demonstrated satisfactory predictive efficacy. In clinically relevant pathologic stage, histologic grade, and T stage, the risk scores obtained based on this signature showed statistically significant difference. The high- and low-risk groups exhibited difference in the tumor immune infiltrating cells, immune checkpoint gene expression, and sensitivity to chemotherapy. In sum, the prognostic signature based on the m6A-related lncRNAs can effectively predict the prognosis of patients and might provide a new vista for the chemotherapy and immunotherapy of HCC.